PENGARUH KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI ADIWANA ARYA VILLA - Nyoman Surya Wijaya; Ni Kadek Bella Milena (Sekolah Tinggi Pariwisata Mataram, 2023)
In the midst of the current development of the tourism industry, hotels are required to continue to improve their services to be able to compete amid the rapidly growing growth of hotels and other accommodations. Employee performance is an aspect that can affect the course of the tourism industry, so it is important for accommodation businesses to pay attention to factors that can improve employee performance. This study aims to determine the effect of competence and communication on employee performance at Adiwana Arya Villa partially. The research period starts from February to July 2022. The data collection techniques used are observation, interviews with three employees from different departments, literature study, and distributing questionnaires to a sample of 43 respondents. The respondents were taken using the saturated sample technique or using the entire population as the research sample. The results of the questionnaire were then analysed quantitatively, including: validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing through t test, and analysis of the coefficient of determination (R2). The results showed that: (1) competence has a positive and significant effect on employee performance with a sig value of 0.000 <0.05. (2) Communication has a positive and significant effect on employee performance with a sig value of 0.000 <0.05. The coefficient of determination is 95.1%, while the remaining 4.9% is influenced by other factors not examined in this study.